PERAN GURU PAI DALAM MENGEMBANGKAN KECERDASAN SPRITUAL SISWA DI SMP NEGERI 1 TIKUNG - Hengki; Intan Ayu; Mahbub Junaidi (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2025)
The Islamic Education (PAI) teachers play a crucial role in fostering students’ spiritual intelligence at SMP Negeri 1 Tikung, which helps them understand the meaning of life, distinguish between right and wrong, and develop positive behaviors. This study employs a qualitative descriptive approach, focusing primarily on PAI teachers as the main subjects. Data were collected through observation, interviews, and documentation, with sources including teachers, the school principal, students, as well as references from books and journals. Data analysis was conducted through data reduction, presentation, and conclusion drawing. The study revealed several key findings: (1) supporting factors for the teachers’ roles include collaboration with the principal and fellow teachers, as well as support from regulations and the school’s vision and mission. Conversely, inhibiting factors consist of low parental awareness and limited school programs focused on developing students’ spiritual intelligence; (2) students’ spiritual intelligence is relatively high in terms of socializing and adapting, yet remains low in self-awareness and in formulating personal vision and mission; (3) PAI teachers perform various functions, including as instructors, class leaders, mentors, classroom managers, motivators, and evaluators. However, students’ awareness in applying the learning to daily life still requires improvement. Data analysis was carried out through data reduction, data presentation, and conclusion drawing.